Formation of Ethnocultural Tourism Clusters in Russia-Kazakhstan Borderline Territory - BANСEROVA, O. L.; KASIMOVA, A. R. (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
The purpose of the paper is to explore the region’s tourism potential and to identify items of material and intangible cultural heritage for the formation of ethnocultural centers and ethnocultural clusters. The paper outlines the concept of cultural heritage and its role for ethnocultural tourism. Stages of evolution of the concept are described starting from the 1980-ies when it referred only to material objects, particularly, historical and architectural monuments and sites, and up to the inclusion of intangible items in the early 21st century, which was marked by interest in the material processing methods, crafts, household and economic patterns, rites and customs of different ethnic groups. The study is focused on the borderline regions of Russia and Kazakhstan where the patterns of local peoples are most distinctive. As a result of the research, a map of ethnic settlements in the discussed region was drawn, and it was established that husbandry relied on household and distant-pasture cattle breeding, which emerged in the territory as early as the Bronze Age. The planning structure of a private farm, its elements and functional interrelation of buildings and production structures were determined, and the conclusion was drawn that, given the sustained ancient traditional household practices, the researched settlements were of interest for tourism and could serve as sites of ethnocultural tourism and provide a ground for the formation of ethnocultural establishments.